1998
DOI: 10.1074/jbc.273.24.14738
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-Dehydroxyvitamin D3 Synergism toward Transforming Growth Factor-β1-induced AP-1 Transcriptional Activity in Mouse Osteoblastic Cells via Its Nuclear Receptor

Abstract: TGF-␤11 is locally produced by osteoblasts and accumulates abundantly in bone matrix tissue (1-3). This local cytokine plays an important role as a "coupling factor" in bone remodeling (4 -7). We (8, 9) previously demonstrated that TGF-␤1 is a potent activator of AP-1, a transcriptional factor that is a heterodimer of FOS and JUN proteins, in mouse osteoblastic MC3T3-E1 cells. AP-1 activates the transcription of target genes by binding to specific promoter elements called TRE. In fact, several studies (10 -16)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 58 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…Until now, two large regions of the OPN promoter have been involved in OPN regulation; the Ϫ1000 to Ϫ700 region is mainly a target for hormones (16,38), whereas the Ϫ270 to ϩ1 region has been shown to be activated by various transcription factors, including AP-1 (15). AP-1 seems to be a common element in the activation of OPN expression by growth factors, because it has been involved in FGF-2-and TGF␤-induced OPN expression in osteoblasts (39,40). Moreover, cis-regulating elements (Lef-1, Ets, and c-Jun) located upstream of Ϫ1000 were involved in the basal expression of OPN in breast cancer cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, two large regions of the OPN promoter have been involved in OPN regulation; the Ϫ1000 to Ϫ700 region is mainly a target for hormones (16,38), whereas the Ϫ270 to ϩ1 region has been shown to be activated by various transcription factors, including AP-1 (15). AP-1 seems to be a common element in the activation of OPN expression by growth factors, because it has been involved in FGF-2-and TGF␤-induced OPN expression in osteoblasts (39,40). Moreover, cis-regulating elements (Lef-1, Ets, and c-Jun) located upstream of Ϫ1000 were involved in the basal expression of OPN in breast cancer cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (11,19,20,(47)(48)(49)(50)(51) have shown that osteogenic and osteolytic factors are able to stimulate expression of the c-fos and c-jun genes in ostoblastic cells. We have also previously shown that TNF-α is able to stimulate expression of c-fos and c-jun and to activate AP-1 in mouse osteoblastic MC3T3-E1 cells (11,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylated form of SMADs forms stable complexes with SMAD4 and these complexes translocate into nucleus where they activate transcription. Recently, TGF-ß has been shown to act cooperatively with vitamin D 3 , indicating a cross-talk between these two signaling pathways (Yoshizawa et al, 1997;Takeshita et al, 1998). The mechanism of synergism between TGF-ß and vitamin D 3 appears to be mediated by SMAD3, but not SMAD2 (Yanagisawa et al, 1999).…”
Section: mentioning
confidence: 99%